Factors related to Endocrine Disruptors Exposing Behaviors in Mothers of Infants - Su Kyung Kim; SoMi Park (Korean Society of Women Health Nursing, 2017)
PURPOSE: The purpose of this study was to examine factors associated with behaviors of mothers that expose their infants to endocrine disruptors. The PROCEED model was used as a theoretical basis for the study. METHODS: This correlational study included 120 mothers with infants between the ages of 1 month to 36 months. Participants were recruited through the maternal community web-site of mothers of infants in W city. RESULTS: There was a significant negative correlation among experience of mothers who had participated in environmentally friendly activities, the health status of the infants perceived by the mother, and behaviors of mothers that exposed infants to endocrine disruptors. The factors based on PROCEED model explained 15.3% of the behaviors by mothers that exposed infants to endocrine disruptors. CONCLUSION: It is necessary to develop and provide educational programs that include detailed information on relationship of endocrine disruptors to children's health.